Plasmonic Material Engineering for Targeted Therapeutics. Issue 17 (6th July 2020) - Florentsen, Christoffer D.; Moreno‐Pescador, Guillermo S.; Kjær, Andreas; Oddershede, Lene B.; Bendix, Poul Martin
Abstract: Nanomedicine approaches based on targeted delivery of nanoparticles have enormous therapeutic potential. For this to succeed, the nanoparticles, possibly functionalized or activatable by lasers, need to reach their target in the organism and preferably accumulate at this target. However, administration of nanoparticles in vivo results in rapid clearance of the particles by the immune system, thus preventing the nanomedicine in reaching its target. Passivation by polymer coatings has provided some success, but has not been sufficient to transform nanomedicine into an effective therapy. Recently, a new approach has been adopted which utilizes native cellular membranes for coating of nanoparticles. Motivated by the signaling and recognition capabilities of natural cell membranes, it is now feasible to produce nanoparticles with both immune evasive and tumor targeting abilities. Circulation times are dramatically enhanced by natural membrane coatings allowing significant increase in the passive accumulation by the enhanced permeability and retention effect. Membrane coating of nanoparticles provides a promising new development for advanced nanoparticle photothermal therapy (PTT). Here, the recent advances and challenges facing this new type of nanoparticle technology, bridging advanced optical properties with bio‐compatibility, are reviewed with a focus on membrane coating of plasmonic nanoparticles which has shown great promise in PTT. Abstract : Targeted delivery of optically activatable nanoparticles has enormous therapeutic potential. For this to succeed, the nanoparticles need to reach their target in the organism and preferably accumulate. New approaches utilize native cellular membranes for coating of plasmonic nanoparticles, thus making them evade the immune system and reach their target. This new technology is reviewed here, bridging advanced optical properties with bio‐compatibility.